Crowd Manager during Pandemic using Video Analytics - et. al., Anjana Seby, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As the COVID-19 pandemic sweeps through the world, we are in need of a system that can manage the flow of people. With the increase of Covid-19 cases, crowds need to be monitored, be it in a public place or in a building. Human monitoring can be quite tiresome and expensive, making way for the upcoming of automated crowd monitoring systems. In this paper, a framework for detection and analysis of crowd flow is proposed. The automated crowd flow analysis and mask detection in buildings eliminates the need for manual monitoring